Laserstrahlumformen von Aluminiumwerkstoffen - Beeinflussung der Mikrostruktur und der mechanischen Eigenschaften - Merklein, Marion (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2001)
Laser beam forming as a flexible shaping process in combination with the lightweight aluminum material represents a particular challenge for the engineering sciences. The investigation and description of the effects of short-term heating on the component and its mechanical properties enable the process to be designed based on the material, thereby expanding the industrial potential laser beam forming for rapid prototyping and small series productio